Simulation of neutron background for a dark matter search experiment at JUSL. (21st June 2021) - Banik, S.; Kashyap, V.K.S.; Ghosh, S.; Dutta, S.; Mohanty, B.; Meghna, K.K.; Bhattacharjee, P.; Saha, S.
Abstract: Dark matter search experiments demand a low to ultralow radiation background to operate. It is very important to understand the nature of the radiation background including knowledge about the sources contributing to it. Sometimes, evaluation of the background becomes very specific to the site chosen for the experiment, and also to the experimental configuration. A dark matter search experiment is proposed to be set up at the Jaduguda Underground Science Laboratory (JUSL) in India. The laboratory will be located inside an existing mine with 555 m of vertical rock overburden. Neutrons produced from (α, n) reactions, spontaneous fission of natural radioactive impurities in the rocks, and also from cosmic muon-induced reactions are considered as the main background which can affect the sensitivity and outcome of the experiment. In this work, simulations based on GEANT4 are done to understand both the radiogenic neutron background caused by natural radioactivity of the surrounding rock and the cosmogenic neutron background due to interactions of the deeply penetrating cosmic muons with the rock material. The muon flux in the cavern is obtained to be 4.49(±0.25)×10 -7 cm -2 s -1 and the fluxes of radiogenic and cosmogenic neutrons above an energy threshold of 1 MeV in the cavern are obtained to be 5.75(±0.69)×10 -6 cm -2 s -1 and 7.25(±0.40)× 10 -9 cm -2 s -1 respectively. The values obtained are comparable with estimates and measurements from DAMA, WIPP, and dark matter experiments at Boulby mine. The effectiveness of different shielding materials is also investigated to obtain the best possible neutron background reduction for a dark matter search experiment at JUSL. We also estimate the sensitivity of a CsI based detector for Weakly Interacting Massive Particle (WIMP) dark matter search at JUSL considering the estimated neutron background.